2017
DOI: 10.1002/ange.201703492
|View full text |Cite
|
Sign up to set email alerts
|

Modular Assembly of Reversible Multivalent Cancer‐Cell‐Targeting Drug Conjugates

Abstract: Herein is described anew modular platform for the construction of cancer-cell-targeting drug conjugates.T ripodal boronate complexes featuring reversible covalent bonds were designed to accommodate ac ytotoxic drug (bortezomib), poly(ethylene glycol) (Peg) chains,a nd folate targeting units. The B-complex core was assembled in one step,proved stable under biocompatible conditions,n amely,i nh uman plasma (half-life up to 60 h), and underwent disassembly in the presence of glutathione (GSH). Stimulus-responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…22 The binding complex is equipped with (1) small spatial requirement, (2) fast binding kinetics and (3) pH-responsiveness within the physiological range (5.0−7.4). 23 Hence, its dynamic covalent binding capabilities have been applied broadly in therapeutics, 24 biosensors, 25,26 stimulus responsive ligation tools 27 and as self-regenerative materials. 28,29 Herein, we propose that BA/ CA motifs in a binary sequence would encode molecular recognition in a stimulus responsive fashion.…”
mentioning
confidence: 99%
“…22 The binding complex is equipped with (1) small spatial requirement, (2) fast binding kinetics and (3) pH-responsiveness within the physiological range (5.0−7.4). 23 Hence, its dynamic covalent binding capabilities have been applied broadly in therapeutics, 24 biosensors, 25,26 stimulus responsive ligation tools 27 and as self-regenerative materials. 28,29 Herein, we propose that BA/ CA motifs in a binary sequence would encode molecular recognition in a stimulus responsive fashion.…”
mentioning
confidence: 99%
“…Thus, 51 in the presence of glutathione releases 52 which will undergo oxidation and self-immolative cleavage to afford 50 (Scheme 10). 95 Again, the modular approach for assembling the molecules greatly facilitates development of a glutathione triggered release of the cytotoxic drug Bortezomid. 95 A model study identified the cleavage products (Scheme 11) and led to a proposal for the mechanism of release of the boronic acid.…”
Section: Reviewmentioning
confidence: 99%
“…95 Scheme 10 Glutathione/hydrogen peroxide induced self-immolative release of a fluorescent coumarin. 95 Scheme 9 Hydrogen peroxide induced self-immolative release of a nitrogen mustard. [91][92][93]…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation